ANALISIS YURIDIS TERHADAP PENYELESAIAN PERSELISIHAN PEMUTUSAN HUBUNGAN KERJA (KASUS PUTUSAN NOMOR: 28/pdt.Sus-PHI/2020/PN.Tpg) - Tresiaty Sibarani; Yogo Pamungkas (Fakultas Hukum Universitas Trisakti, 2021)
PT Aswin Transportation Wisata (Defendant) unilaterally terminated the employment relationship with the Workers (Plaintiff) via text message on the grounds that the Covid-19 pandemic never ended so that the Defendant could not pay the Plaintiffs' wages each month. The problem of this research is whether the settlement of termination of employment between the Plaintiffs against PT Aswin Wisata Transportation is in accordance with statutory regulations and whether the Judge's Decision on the settlement of the termination of employment dispute between the plaintiffs against PT Aswin Tourism Transportation in accordance with the laws and regulations? To answer this question, a normative juridical research was carried out, which is descriptive-analytical by using secondary data which was analyzed qualitatively by deductive method as a conclusion. The results of this study are the process of settling industrial relations disputes and the Judge's decision in decision Number 28/Pdt.Sus-PHI/2020/PN.Tpg not in accordance with the PPHI Law.